A novel mechanocatalytical reaction system driven by fluid shear force for the mild and rapid pretreatment of lignocellulosic biomass. (1st July 2022) - Li, Jingxue; Wang, Yingxiong; Zhu, Wanbin; Chen, Shanshuai; Deng, Tiansheng; Ma, Shuaishuai; Wang, Hongliang
Graphical abstract: Highlights: Fluid shear as a novel force was effective in driving biomass pretreatment reactions. 90% of lignin and hemicellulose in biomass could be separated by fluid shearing. Glucose yield via enzymatic hydrolysis tripled after fluid-shear pretreatment. The obtained lignin kept a structure similar to that of native lignin. Mechanism of biomass pretreatment by fluid shearing was preliminarily revealed. Abstract: Pretreatment is the initial stage of lignocellulosic biorefinery process, but is limited by the time-consuming processes, harsh conditions and/or undesirable products. Herein, a mild (<60 °C) and highly efficient pretreatment strategy is developed. The novel mechanocatalytical reaction system driven by fluid shear force helps to exfoliate cellulose from lignocellulose, and the heat generated by the shear process can be used to precipitate and recover the dissolved cellulose from the precooled NaOH/urea solution. The regenerated cellulose shows satisfying crystal structure (cellulose II), significantly decreased crystallinity and nearly tripled enzymolysis glucose yield. Almost 90% of lignin and hemicellulose could be rapidly separated. The separated lignin shows a nearly native structure with 64% β-O-4 linkage, which is even higher than the ball-milling lignin (60%). This research provides a theoretical guidance for the mild pretreatment of lignocellulosic biomass, which will push the application of mechanocatalytical reaction system in biorefinery processes on a large scale.